Praxes for Culturally Responsive Teaching in Basic and Higher Education - Pecson, Ryan R; Morales, Frank Elie V (Journal of Basic Education Research, 2026)
Purpose of the study: Learners’ diversity and individuality demand contextualized and inclusive education anchored on their diversified approach, catering to their academic, social, and cultural contexts. Responding to that reality, the present study explored the praxes for culturally-responsive teaching (CRT) in basic and higher education in the Philippines as an input for the proposal of an inclusive learning plan for novice educators. Methodology: Using the descriptive qualitative approach of research, twelve novice educators were purposively selected to participate in the semi-structured interviews, wherein the results were analyzed using thematic analysis. Main Findings: The study highlighted CRT as an essential practice that fosters inclusive practice, enhances learning by valuing cultural knowledge and respecting different student histories. The research emphasized the necessity of embedding culturally-responsive approaches like improving community engagement and personalizing learning to fire up relevance and access to learning. Novelty/Originality of this study: The study introduces an output (inclusive learning plan) that can guide novice educators toward their inclusive learning practices and advocacies. As part of strengthening the role in induction programs for novice educators, embed an inclusive learning plan in these programs to develop the skills novice educators need to create supportive and culturally sensitive learning environments.